Developing and disseminating knowledge on medicinal plants - Martins, Monik Compagnoni; Garlet, Tânea Maria Bisognin (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2016)
This study aimed to inform the public about medicinal plants. Throughout the work occurred publications in a news journal, leaflet distribution and dissemination of a video content with plain on the use of medicinal species. Questionnaires were administered to 266 people, who mentioned 73 medicinal species, citing its used parties and other uses. You can check with the questions asked to the academic interviewed that most of them use medicinal plants only in cases of diseases and their knowledge is coming from the oldest family.